Aggrecan governs intervertebral discs development by providing critical mechanical cues of the extracellular matrix - Empere, Marta; Wang, Xujia; Prein, Carina; Aspberg, Anders; Moser, Markus; Oohashi, Toshitaka; Clausen-Schaumann, Hauke; Aszodi, Attila; Alberton, Paolo (Frontiers in Bioengineering and Biotechnology, 2023)
Aggrecan (ACAN) is localized in the intervertebral disc (IVD) in unique compartment-specific patterns where it contributes to the tissue structure and mechanical function together with collagens. The extracellular matrix (ECM) of the IVD undergoes degenerative changes during aging, misuse or trauma, which inevitably alter the biochemical and biomechanical properties of the tissue. A deeper understanding of these processes can be achieved in genetically engineered mouse models, taking into account the multifaceted aspects of IVD development. In this study, we generated aggrecan insertion mutant mice (AcaniE5/iE5) by interrupting exon 5 coding for the G1 domain of ACAN, and analyzed the morphological and mechanical properties of the different IVD compartments during embryonic development. Western blotting using an antibody against the total core protein failed to detect ACAN in cartilage extracts, whereas immunohistochemistry by a G1-specific antibody showed week weak signals in vertebral tissues of AcaniE5/iE5 mice. Homozygous mutant mice are perinatally lethal and characterized by short snout, cleft palate and disproportionate dwarfism. Whole-mount skeletal staining and µ-CT analysis of AcaniE5/iE5 mice at embryonic day 18.5 revealed compressed vertebral bodies with accelerated mineralization compared to wild type controls. In AcaniE5/iE5 mice, histochemical staining revealed collapsed extracellular matrix with negligible sulfated glycosaminoglycan content accompanied by a high cellular density. Collagen type II deposition was not impaired in the IVD of AcaniE5/iE5 mice, as shown by immunohistochemistry. Mutant mice developed a severe IVD phenotype with deformed nucleus pulposus and thinned cartilaginous endplates accompanied by a disrupted growth plate structure in the vertebral body. Atomic force microscopy (AFM) imaging demonstrated a denser collagen network with thinner fibrils in the mutant IVD zones compared to wild type. Nanoscale AFM indentation revealed bimodal stiffness distribution attributable to the softer proteoglycan moiety and harder collagenous fibrils of the wild type IVD ECM. In AcaniE5/iE5 mice, loss of aggrecan resulted in a marked shift of the Young’s modulus to higher values in all IVD zones. In conclusion, we demonstrated that aggrecan is pivotal for the determination and maintenance of the proper stiffness of IVD and vertebral tissues, which in turn could play an essential role in providing developmental biomechanical cues.